Update on Dementia 2016
DOI: 10.5772/64233
|View full text |Cite
|
Sign up to set email alerts
|

Clusterin (APOJ) in Alzheimer’s Disease: An Old Molecule with a New Role

Abstract: Clusterin (CLU), initially identified in 1983 as a "clustering factor" in ram rete testis fluid, is a multifaceted protein that was rediscovered and subsequently renamed eight times from 1983 to 1992. CLU exists as multiple protein isoforms including the 80 kDa glycosylated mature/secreted form of CLU (mCLU) and the smaller non-modified nuclear and intracellular forms of CLU (nCLU and icCLU, respectively). These isoforms, which are expressed at the highest levels in the brain, are suggested to play distinct ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 144 publications
(169 reference statements)
0
5
1
Order By: Relevance
“…Over half of the glycoforms were sialylated, and our results suggested a high degree of microheterogeneity of glycosylation at Thr 212 (Figure c). Despite APOJ having been shown to carry several PTMs such as N-glycosylation, ubiquitination, and phosphorylation, O-glycosylation has not been reported before. In our study, seven glycosites were found among three states, and only Thr 105 and Ser 210 were glycosylated in all three states (Figure d). Compared to ApoE, glycosylation on ApoJ showed a higher degree of macro-heterogeneity, and the change in site occupancy may play an important role in AD progression …”
Section: Resultscontrasting
confidence: 51%
“…Over half of the glycoforms were sialylated, and our results suggested a high degree of microheterogeneity of glycosylation at Thr 212 (Figure c). Despite APOJ having been shown to carry several PTMs such as N-glycosylation, ubiquitination, and phosphorylation, O-glycosylation has not been reported before. In our study, seven glycosites were found among three states, and only Thr 105 and Ser 210 were glycosylated in all three states (Figure d). Compared to ApoE, glycosylation on ApoJ showed a higher degree of macro-heterogeneity, and the change in site occupancy may play an important role in AD progression …”
Section: Resultscontrasting
confidence: 51%
“…For years sitting on the Bback shelf^of cell death research, necrotic cell death now emerges demonstrating to be a more and more coordinated and sophisticated cell death mechanism with a huge potential in biomedical research (Vanden Berghe et al 2014). Involved in this setting is the extracellular chaperone clusterin (CLU), also known as apolipoprotein J (APOJ), which is highly correlated with necrosis, tissue degeneration, and apoptosis (Rohne et al 2016;Woody and Zhao 2016). CLU is found to exert a cytoprotective role by helping to heal damaged tissues, clear the extracellular space from apoptotic cells, protein aggregates, and cellular debris (Baiersdorfer et al 2010;Bartl et al 2001;Cunin et al 2016;Lee et al 2011;Viard et al 1999;Wilson and Zoubeidi 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Since an upregulation of CLU (APOJ) has been observed in cells challenged with necrotic cell lysates (Bach et al 2001), we began using this gene to study the cellular response towards these exogenous stress conditions. At first, we focused on putative signaling pathways that have been described to upregulate CLU, such as the JNK/SAPK and the NF-κB signaling pathway, as well as the contribution of a heat shock response (Prochnow et al 2013;Rohne et al 2016;Viard et al 1999;Woody and Zhao 2016).…”
Section: Exposure Of Vital Cells To Necrotic Cell Lysates Triggers Jnmentioning
confidence: 99%
“…Clusterin (CLU) is currently rated as the third most predominant genetic risk factor associated with the development of LOAD (Alzforum Networking, 2019). Specifically, a number of clinical studies have confirmed an association between CLU alleles (primarily rs11136000, c allele) and increased risk for LOAD (reviewed in Woody and Zhao, 2016), including two of the largest human genome-wide association studies conducted to date (Harold et al, 2009; Lambert et al, 2009). Although the CLU gene was initially discovered over three decades ago (Fritz et al, 1983; Léger et al, 1987; Murphy et al, 1988), a complete understanding of this gene and the translated protein isoforms is still missing from the current literature.…”
Section: Discussionmentioning
confidence: 99%